The Impact of Driver Behavior on Accident Rates in a Fleet Management System - Denise Fortunate Aber (Uganda Christian University, 2023)
This study investigated the impact of driver behavior on accident rates in a fleet management system, focusing on the case of Century Bottling Company Uganda. The objectives of this study were to identify effective strategies for promoting safe driving behavior, the influence of organizational safety culture on driver behavior and to examine the relationship between driver behavior and accident rates in a fleet management system. The study employed a mixed-methods approach, which combined quantitative analysis of accident data and driver behavior metrics with qualitative insights gathered through questionnaires distributed to the fleet and distribution department of Century bottling Company. The population of our study consisted of fifty seven employees under the distribution and fleet department hence giving us a sample size of fifty two respondents who were chosen using the random sampling technique and all of them filled in the questionnaires that were distributed to them. The data collected was analyzed using MS excel and SPSS which helped in the interpretation of the findings. The findings revealed a clear association between driver behavior and accident rates within the fleet management system identifying risky driving behaviors, such as speeding, over taking and distracted driving as significant contributors to accidents. The research findings also showed that the company had put effective strategies like rewarding of the best drivers, attaching telematics such as GPS and cameras to help with tracking of drivers” behaviors all which have helped in reducing accident rates in the company. Organizational safety culture emerged as a crucial factor in shaping driver behavior. A positive safety culture, driven by strong leadership commitment, employee involvement, effective communication, comprehensive training programs, and a system of accountability, fostered a sense of responsibility among drivers and encouraged adherence to safety guidelines. The findings also indicate a strong linear relationship between driver behavior and accident rates at century bottling company.( Correlation is significant at the 0.01 level (2-tailed). Based on the research findings, several recommendations were proposed to promote safe driving behaviors and these included the implementation of incentive programs to reward and reinforce safe driving practices, fostering a culture of safety through leadership commitment and involvement, enhancing communication channels to encourage the reporting of safety concerns, providing comprehensive driver training programs on defensive driving techniques and hazard perception, By adopting these strategies, the company can effectively reduce accident rates and enhance driver safety in their fleet management system.
This is a dissertation.